Aggressions of Communism Through Indonesian’s Literary Works - Mamik Tri Wedawati; Diana Budi Darma (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2018)
This study focused on aggression that enriched literary texts in Indonesian Communism. Initially, analysis was triggered by a preliminary input from classes and tasks that were given in similar topics and were identified important information. There were three facts that were constructed, which were indirect, passive and harsh expressions in literary texts. They were evidencee of change in understanding Communism in millennium era. To elaborate them, two statement of the problems were chosen, which were manifestation and code communication in selected texts. Sorting raw data into a commounicative data was done through applying Intertextuality. The methodology required a qualitative procedure which data were taken from varied sources such as short stories, articles, journals, and text book , which were in a form of printed or softfile productions. The results encouraged researches to comprehend aggression as not only a form of actions but also mental attitude. Others that are interested in similar contemporary texts and aggressions in general should include this in other analysis under Communism.